Response of Five Wild Colocynth [Citrullus colocynthis ( L.) Schrad.] Ecotypes to Sowing Date, Regarding Their Growth, Seed Yield and Seed Oil Content - Eldosh, Zeinab E. E. M.; Elsiddig, Marmar A.; Ali, Abdalla Mohamed (University of Khartoum Journal of Agricultural Sciences, 2022)
The rational exploitation of medicinal and aromatic plants can be through cultivation to conserve them as potential high economic value crops. The objective of this research was to evaluate the response of wild ecotypes of colocynth plants to sowing date regarding their growth, seed yield and seed oil content. The layout of the experiment was a split plot design with three replications. Treatments were two sowing dates and five wild ecotypes. Sowing dates of mid-July (autumn) And mid-March (summer) were randomized in the main plots. The five ecotypes were randomized in the subplots. The experiment was carried out for two seasons, 2013/14 and 2014/15. Parameters measured were ,days to 50 % emergence, days to 50 %flowering, mean number of fruits per plant, mean number of seeds per fruit, weight of 1000 seeds, seed yield and seed oil content. Number of days to 50 % emergence was significantly different between sowing dates only in the first season; however ecotypes were significantly different in both seasons. Number of days to 50 % flowering was not significantly different between sowing dates in both seasons, but was significantly different among ecotypes. Numbers of fruits per plant, number of seeds per fruit and seed yield were significantly different between sowing dates and among ecotypes in both seasons. Most importantly, mean seed oil content of cultivation (sowing dates) was higher (16.4 %) than wild seed oil content (12.05). In conclusion, cultivation of colocynth was advantageous regarding plant growth, seed yield and oil content. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">